The Renaissance of Roman colonization Carlo Sigonio and the making of legal colonial discourse - Pelgrom, Jeremia; Weststeijn, Arthur (History and theory of international law., 2020)
The colonization policies of Ancient Rome followed a range of legal arrangements concerning property distribution and state formation, documented in fragmented textual and epigraphic sources. When antiquarian scholars rediscovered and scrutinized these sources in the Renaissance, their analysis of the Roman colonial model formed the intellectual background for modern visions of empire. What does it mean to exercise power at and over distance? This book foregrounds the pioneering contribution to this debate of the great Italian Renaissance scholar Carlo Sigonio (1522/3-84). His comprehensive legal interpretation of Roman society and Roman colonization, which for more than two centuries remained the leading account of Roman history, has been of immense (but long disregarded) significance for the modern understanding of Roman colonial practices and of the legal organization and implications of empire. Bringing together experts on Roman history, the history of classical scholarship, and the history of international law, this book analyzes the context, making, and impact of Sigonio's reconstruction of the Roman colonial model. It shows how his legal interpretation of Roman colonization originated and how it informed the development of legal colonial discourse, from imperial reform and colonial independence in the nascent United States of America to Enlightenment accounts of property distribution. Through a detailed analysis of scholarly and political visions of Roman colonization from the Renaissance to today, this book shows the enduring relevance of legal interpretations of the Roman colonial model for modern experiences of empire.